1979
DOI: 10.1042/bj1820361
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate metabolism in the heart. Regulatory properties of rabbit cardiac adenylate deaminase

Abstract: The kinetic properties of a 300-fold purified cardiac AMP deaminase were studied and compared with those of the corresponding enzyme from skeletal muscle. The heart enzyme is activated by ATP and less efficiently by ADP, and is inhibited by Pi, phosphocreatine and GTP. ATP, even at micromolar concentrations, is able to abolish the effects of the inhibitors. The affinity of the enzyme for AMP is low in the absence of activators (Km 3.1 mM), but, in the presence of ATP, becomes as high as that of skeletal-muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
2
18
1
Order By: Relevance
“…Although both require millimolar K+ for full activity, the former is more readily activated by bivalent cations than the latter [9]. The apparent Km of 5.8 mM AMP for rabbit cardiac AMP deaminase is greater than the Km of 0.3-0.7 mM generally reported for (rabbit) skeletal-muscle AMP deaminase [29,35], implying that the cardiac isoform has much lower substrate affinity. AMP deaminase activity in enriched cardiac preparations reaches half-maximal reaction velocity at 2-13 mM AMP [23,24,27], suggestive of the low-millimolar Km that we have…”
Section: Discussionmentioning
confidence: 99%
“…Although both require millimolar K+ for full activity, the former is more readily activated by bivalent cations than the latter [9]. The apparent Km of 5.8 mM AMP for rabbit cardiac AMP deaminase is greater than the Km of 0.3-0.7 mM generally reported for (rabbit) skeletal-muscle AMP deaminase [29,35], implying that the cardiac isoform has much lower substrate affinity. AMP deaminase activity in enriched cardiac preparations reaches half-maximal reaction velocity at 2-13 mM AMP [23,24,27], suggestive of the low-millimolar Km that we have…”
Section: Discussionmentioning
confidence: 99%
“…Deaminase activity of AMPD is known to be increased by optimal pH, ATP, ADP, NADH, and phosphorylation by PKC and to be inhibited by inorganic phosphate and GTP [30,31]. Since it has been reported that several PKC isoforms are activated in diabetic hearts [32] and that AMPD activity is increased in a model of type 1 diabetes mellitus (T1DM) [33], we examined possible role of PKC in increased AMPD activity in OLETF.…”
Section: Up-regulated Ampd Activity and Its Functional Impact In Diabmentioning
confidence: 99%
“…Removal of ATP and ADP or withdrawal of their inhibition by increases in Mg++ ions would increase the 5'-nucleotidase activity. Flux towards adenosine would be controlled by the relative activity of AMPda and 5'-nucleotidase, as is postulated for the rabbit heart (Barsacchi et al, 1979). From the above values of AMPda and 5"Kleotidase activity in rabbit arterial tissue, the flux on complete activation of both enzymes is expected to be towards adenosine.…”
mentioning
confidence: 98%